Predictors of postoperative infectious complications after partial nephrectomy: Analysis at a referral institution - Riccardo Bertolo; Francesco Ditonno; Alessandro Veccia; Francesca Montanaro; Francesco Artoni; Alberto Baielli; Michele Boldini; Davide Brusa; Sonia Costantino; Marcella Sibani; Vincenzo De Marco; Filippo Migliorini; et al. (Asian Journal of Urology)
Objective: Infectious complications after partial nephrectomy (PN) remain a significant concern. We aimed to analyze predictive factors of postoperative infectious complications (PICs) occurring after PN. Methods: Data on patients undergoing PN for renal masses between January 2018 and May 2023 were retrieved from prospectively maintained institutional database and retrospectively analyzed. Patients were stratified into two groups based on the occurrence of PICs during admission for PN. A PIC was defined by clinical and/or imaging findings of an infectious process plus microbial isolation upon culture examination. Multivariable logistic regression analysis after adjusting for potential confounders evaluated predictors of a PIC. Results: Six-hundred and twenty-seven patients underwent PN; rough incidence of PICs was 11%, with median time to PIC onset of 1 (interquartile range 0–3) day. Compared to patients without PIC events, the PIC group showed a significantly higher proportion of open surgeries (54% vs. 20%, p<0.001), bleeding events (23% vs. 10%, p<0.01), postoperative transfusion (19% vs. 5.0%, p<0.001), and urinary leakage (4.2% vs. 0.18%, p=0.01), and a statistically significantly higher median hemoglobin drop from baseline (−2.6 g/dL vs. −1.7 g/dL, p=0.001). At multivariable logistic regression, the odds of experiencing a PIC were statistically significantly lower after minimally-invasive surgery compared to open surgery (odds ratio 0.32, 95% confidence interval 0.17–0.59), and higher for patients who received transfusion (odds ratio 1.68, 95% confidence interval 1.10–2.54). Conclusion: We underlined factors that impact the occurrence of PICs and, consequently, duration of hospitalization following PN. By addressing these predictors, clinicians can promote enhanced patient recovery.